1992
DOI: 10.1056/nejm199202273260902
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Sludge as a Cause of Acute Pancreatitis

Abstract: Biliary sludge is an underestimated cause of acute idiopathic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
201
1
15

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(225 citation statements)
references
References 16 publications
2
201
1
15
Order By: Relevance
“…Subjects treated with placebo showed a significant increase in the number of severely damage mitochondria after reperfusion, whereas the number of damaged and necrotic myocytes also increased significantly in these subjects after infusion. No such damage to mitochondria or myocytes was observed in the taurine treated subjects (Lee et al, 1992). The use of supplemental taurine as a physiological protective against lipid peroxidation was advocated by Gordon et al (1986) who demonstrated the protection of hamaster bronchioles from acute NO 2 -induced alterations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Subjects treated with placebo showed a significant increase in the number of severely damage mitochondria after reperfusion, whereas the number of damaged and necrotic myocytes also increased significantly in these subjects after infusion. No such damage to mitochondria or myocytes was observed in the taurine treated subjects (Lee et al, 1992). The use of supplemental taurine as a physiological protective against lipid peroxidation was advocated by Gordon et al (1986) who demonstrated the protection of hamaster bronchioles from acute NO 2 -induced alterations.…”
Section: Discussionmentioning
confidence: 91%
“…It was proposed by Gordon et al (1986) and Cardin et al (1999) that the protective activity of taurine may reside in its ability to become chlorinated in the presence of HOCL, thereby preventing the direct attack of this oxidant on cell membranes (Rock et al, 1996). Lee et al (1992) postulated that the protective action of taurine on oxidant-induced damages of tissue components including degradation of hyaluronic acid may be attributed to both its scavenging action on hypochloriate (HOCl) and chloramine and the complex formation of taurine with HOCl or NH2Cl without scavenging action on oxygen free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…It forms a dense layer in the gallbladder. Behaving similarly to gallstones, it may cause acute pancreatitis and similarly, cleaning coledoc using cholecystectomy and ERCP may prevent recurrent pancreatitis attacks [24,25]. Experimental studies have demonstrated that biliary reflux was not a necessity for acute pancreatitis development, and pancreatitis may develop as a result of pancreatic duct obstruction [26].…”
Section: Pathophyisiologymentioning
confidence: 99%
“…This sediment consists of cholesterol crystals, calcium bilirubinate pigment, and other calcium salts [21]. Biliary sludge is usually detected on transabdominal ultrasonography: produces a mobile, low amplitude echo,without acoustic shadow.…”
Section: Biliary Sludge and Microlithiasismentioning
confidence: 99%